2021
DOI: 10.1177/0734242x211003968
|View full text |Cite
|
Sign up to set email alerts
|

A mini-review of heavy metal recycling technologies for municipal solid waste incineration fly ash

Abstract: This mini-review article summarizes the available technologies for the recycling of heavy metals (HMs) in municipal solid waste incineration (MSWI) fly ash (FA). Recovery technologies included thermal separation (TS), chemical extraction (CE), bioleaching, and electrochemical processes. The reaction conditions of various methods, the efficiency of recovering HMs from MSWI FA and the difficulties and solutions in the process of technical development were studied. Evaluation of each process has also been done to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 118 publications
0
5
0
Order By: Relevance
“…The conventional calcined thermal separation process is characterized by low heavy metal separating effect and high-energy consuming. By comparison, all three other methods of thermal separation achieved removal rates above 90%, used additives to facilitate the volatilization on heavy metals, and lowered the calcining temperature. , As a result, the use of additives presents several challenges. Thermal separation of chlorine provides excellent removal of heavy metals with less energy consumption thanks to the use of chlorinating agents, and Chan et al reported complete volatilization of Zn, Pb, Mn, and Cu at 900 °C in a 2% Cl 2 atmosphere.…”
Section: Treatment and Disposal Of Heavy Metals In Fly Ashmentioning
confidence: 99%
“…The conventional calcined thermal separation process is characterized by low heavy metal separating effect and high-energy consuming. By comparison, all three other methods of thermal separation achieved removal rates above 90%, used additives to facilitate the volatilization on heavy metals, and lowered the calcining temperature. , As a result, the use of additives presents several challenges. Thermal separation of chlorine provides excellent removal of heavy metals with less energy consumption thanks to the use of chlorinating agents, and Chan et al reported complete volatilization of Zn, Pb, Mn, and Cu at 900 °C in a 2% Cl 2 atmosphere.…”
Section: Treatment and Disposal Of Heavy Metals In Fly Ashmentioning
confidence: 99%
“…Therefore, the objective of the waste-to-energy and materials approach (Figure 1) is to devise solutions that make the extraction of valuable elements from FA economically attractive. Currently, several techniques, mainly of a thermal or hydrometallurgical nature [51], are under study. The greatest economic potential likely lies in the integration with other operations conducted at the WtE plant: for instance, zinc recovery via acid leaching by reusing effluents from wet flue gas cleaning systems, of which the feasibility at an industrial scale was demonstrated recently [52,53].…”
Section: Valorization Of Bottom and Fly Ash From Conventional Wte Ope...mentioning
confidence: 99%
“…The main treatment methods for FA now include safe disposal in landfills, solidification/stabilization (S/S), separation and extraction, and heat treatment. 5 Out of the various methods used in China for disposing of FA, the S/S technology is considered the most prominent. 6 S/S is a procedure that entails the amalgamation of a fixing agent with an immobilization agent, followed by a reaction conducted under precise conditions to generate a solidified matrix.…”
Section: Introductionmentioning
confidence: 99%